Using paper chart based clinical reminders to improve guideline adherence to lipid management - Hung, Chi-Sheng; Lin, Jou-Wei; Hwang, Juey-Jen; Tsai, Ru-Yi; Li, Ai-Tzu (Journal of evaluation in clinical practice, 2008)
Rationale, aims and objectives  The objective of this study was to apply a paper‐based clinical reminder to improve the adherence to lipid guidelines. Methods  Patients with coronary heart disease (CHD) without lipid‐lowering therapy (LLT) were recruited, and medical records were reviewed. Eligible subjects were randomized; a clinical reminder stating current standards and local insurance policy was stamped on the paper chart in the study group but not in the control. The primary outcome was new LLT subscription in the 6‐month follow‐up period, and the secondary end point was the composite result of LLT or lipid profile check‐up. Results  Ninety‐two patients were assigned to the study group and 102 to the control group. The primary outcome showed no difference at the end of 6 months (OR: 1.70, P = 0.248, 95% CI: 0.69–4.19). The secondary end point was significantly higher in the reminder group (OR: 2.81, P = 0.001, 95% CI: 1.57–5.04). Conclusion  A paper chart based clinical reminder providing update clinical recommendations could modify the doctor's behaviour and improve the attention to lipid levels. However, its effect cannot be transformed into an increase in LLT or a decrease in low‐density lipoprotein level owing to local policy constraint.